Encounters and impressions during more than half a century.1 - Ernst, A. H. (Koers, 1955)
God had ordained that I had to live in and serve many countries in every continent; but more especially Europe and South East Asia. My life experiences of more than a half-century have taught me the absolute need for the European, with his higher culture and way of life, to live incomplete separation or “apartheid” from the natives of Asiatic and African countries; not because they are black or brown or yellow, but because the environment in which they have grown up has produced types of a lower standard of morality and culture.